A Multifaceted Analysis and Misinformation in The French Lieutenant's Woman Concerning the Creationism, Existentialism, and Dualism with Uncertainty of Narrative - Alghanim, Gheni Kadhim Azeez; Noor, Siti Noor Fazelah Binti Mohd (Indian Journal of Information Sources and Services, 2025)
This research paper explores Fowles's masterpiece, The French Lieutenant's Woman, through creationism, existentialism, and dualism. The multiple references to this theme allow the novelist to freely travel through 19th-century British history, existentialist philosophy, and 20th-century literary theory and to use the work as a metaphor to point to reality, triggering readers' understanding of the freedom of existentialism. When analysing the novel's themes of reality, illusion, free will, and fate, the paper highlights how these philosophical perspectives may contribute to a deeper understanding of the narrative. The paper investigates how these frameworks can distract readers and lead to potential doubt and misunderstandings. The paper intends to discover the possibility of different layers gained from each perspective and discuss their limitations in fully capturing the novel's complexity.